MHD instabilities and their effects on plasma confinement in the large helical device plasmas - Toi, K., author; Ohdachi, S., author; Yamamotoa, S., author; Nakajima, N., author; IAEA Fusion Energy Conference (19th : 2002 : France) (Toki, Japan : National Institute for Fusion Science (NIFS), 2002)
PSZJBL